Sufism-inspired multicultural education: pedagogical strategies for fostering social harmony in borderland schools - Kamal, Muhiddinur; Sulong, AbdulRamae; Rashed, Zetty Zuliana; Ahida, Ridha; Rezi, Muhammad (Indonesian Journal of Islam and Muslim Societies, 2026)
T This study highlights the importance of Sufism-based multicultural education in promoting social harmony in schools located in border areas, especially between West Sumatra and North Sumatra. This aspect has been overlooked in many previous studies on multicultural education. Using a qualitative descriptive approach within the framework of the sociology of education, this research shows that integrating Sufism values into the curriculum can improve tolerance, empathy, and respect for diversity. In addition to delivering the curriculum, teachers act as vital role models, instilling spiritual values in students’ daily lives and the school environment. Sufism-based multicultural education also encourages collaboration among schools, communities, and religious institutions to foster an inclusive and harmonious social atmosphere. The findings highlight the importance of the spiritual dimension as a crucial strategy in implementing multicultural education that promotes social cohesion in border regions. Studi ini bertujuan menjelaskan signifikansi pendidikan multikultural berbasis tasawuf dalam membentuk harmoni sosial di sekolah-sekolah yang berada di wilayah perbatasan, khususnya antara Sumatera Barat dan Sumatera Utara. Konteks tersebut selama ini masih terabaikan dalam berbagai studi-studi pendidikan multikultural sebelumnya. Dengan menggunakan pendekatan deskriptif kualitatif dalam kerangka sosiologi pendidikan, penelitian ini menemukan bahwa integrasi nilai-nilai tasawuf ke dalam kurikulum mampu memperkuat nilai-nilai toleransi, empati, dan penghargaan terhadap keberagaman. Selain kurikulum, peran guru sangat penting sebagai teladan dalam menginternalisasikan nilai-nilai spiritual ke dalam kehidupan sehari-hari siswa dan lingkungan sekolah. Pendidikan multikultural berbasis tasawuf juga membangun sinergi antara sekolah, masyarakat, dan lembaga keagamaan dalam menciptakan iklim sosial yang inklusif dan harmonis. Signifikansi studi ini menegaskan pentingnya dimensi spiritual sebagai strategi utama dalam merealisasikan pendidikan multikultural yang mampu memperkuat kohesi sosial di wilayah perbatasan.